Quality of services LoRaWAN satellite communication - Purnama, Iwan; Dwi Putra, Muhammad Taufik; Samsinar, Samsinar; Aulia, Masyitah; Shina, Ibnu; Yuliyus Maulana, Yudi; Benny Louhenapessy, Bendjamin; Dominggus Lekalette, Johanis; Parulian Sitompul, Peberlin; Manik, Timbul; Nendra Wibawa, Lasinta Ari; Prasetyo Adi, Puput Dani; Sinaini, La; Lestari, Pratiwi; Sulaeman, Yaya; Rohman Setiawan, Iwan; Nugraha, Budi; Yati, Emi; Sadiyah, Lilis; Jatmiko, Irwan; Sacipto, Rian; Sariningrum, Ros (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
This research discusses research that focuses on the capabilities of satellitebased LoRa, for satellite positions orbiting in low earth orbit (LEO). The expectation of low power wide area network (LPWAN) satellite can find the quality of transmitting data using LoRaWAN which is part of LPWAN and can provide quality of service (QoS) with high-quality real-time sensor data, low latency, long-range, low-power, no attenuation signal, no problem with obstacles in terrestrial areas, and other benefits that can be widely optimized. This article uses a comprehensive analysis of mathematical calculations as well as precise and accurate simulations for the actual development of satellite-based LPWAN. The satellite-based IoT is unlimited in terms of distance, to provide good services to all IoT users in the world. The comparison with terrestrial measurements is analyzed in detail, especially the signal attenuation factor that causes a lot of signal loss and data is not well received. Several methods are used to help reduce collision data, such as adaptive data rate (ADR) which can reduce collisions by 30%.